EFFECT OF VITAMIN C, E AND SELENIUM ON HAEMATOLOGICAL AND SERUM BIOCHEMISTRY OF ADULT MALE GUINEA PIGS - Bature, Ibrahim; Sani, Gaddafi (FUDMA Journal of Sciences, 2024)
The study was conducted to assess the biopotency of antioxidant supplements on physiological, testicular, and oxidative biomarkers in adult male guinea pigs (Cavia porcellus). A total of 60 adult male guinea pigs of three months of age with an average body weight of 500±20g were randomly allocated into three dietary treatment groups of vitamin C, E and Selenium and each comprised four varying levels with five animals per group in a completely randomized design (CRD). Feed and water was provided ad-libitum. Haematological concentration of guinea pigs in this study indicated a significant (P<0.05) variations in Packed cell volume, Haemoglobin, White blood cell and differential counts of guinea pigs supplemented with varying levels of vitamin C, E and Selenium. The result also indicate a non-significant (P>0.05) difference on Plasma Albumin, Globulin, Total protein, Alanine aminotranferase and Alkaline phosphate of animal supplemented with varying dosage of vitamin E and Selenium. However, a significant (P<0.05) difference occur in Plasma ascorbic acid, Plasma vitamin E, Plasma selenium and Testesterone in guinea pig supplemented with vitamin C, E and Selenium with only exception on Plasma ascorbic acid and Plasma selenium in guinea pigs supplemented with vitamin E and C for Plasma ascorbic acid and Plasma selenium respectively. It could be concluded that vitamin C, E and Selenium can be incorporated into guinea pigs without deleterious effect in both heamatological and serum biochemical profile. Farmers are therefore recommended to use upto 300mg/kg vitamin C, 45mg/Kg vitamin E and 0.3mg/kg selenium in guinea pigs diet for outstanding...